Guide to financial markets - Levinson, Marc. (London : The Economist in association with Profile Books, 2010)
Recent market turbulence makes it clear just how important it is to understand the key markets. This is the definitive guide to why different markets exist, how they operate, and how they are interrelated. Extensively revised and updated, this new edition brings the reader up to date with the latest developments in financial instruments and provides a clear and incisive guide to this increasingly complex world.
Includes index.
oif 22/07/14
Loan
Keywords: Financial markets; Finance; Money market; Stock exchanges; Foreign exchange market; Bond market; Commodity exchanges; Options (Finance); Derivative securities